A compound, a preparation method thereof and its application as an elution-resistant deactivation lithium extraction adsorbent
By introducing specific anions into the aluminum salt lithium adsorbent, an adsorbent with a large layer spacing is solved, and the problems of excessive elution and structural collapse of the aluminum salt lithium adsorbent during the elution process are improved, and its lithium extraction performance is improved. Application value.
Patent Information
- Application Number
- CN202310220012.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-02
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-03-02
AI Technical Summary
The existing aluminum salt lithium adsorbents are prone to excessive elution and structural collapse during the elution process, resulting in a decline in lithium extraction performance and limiting their industrial application value.
By introducing specific anions into the layered structure of the aluminum salt lithium adsorbent, such as CO32-, SO42-, SO32-, PO43-, PO33-, BO43-, DBS-, DS-, etc., an adsorption with a larger layer spacing is formed. The agent inhibits the excessive elution of Li+ and speeds up the ion transfer rate.
The anti-elution inactivation ability of aluminum salt lithium adsorbent is achieved, structural collapse is avoided, adsorption capacity and adsorption rate are improved, and its performance as lithium extracting adsorbent is enhanced.
Smart Images

Figure CN116282111B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of lithium extraction from salt lake brine, and in particular to a compound, a preparation method thereof, and an application thereof as an adsorbent for lithium extraction that is resistant to elution and deactivation. Background Art
[0002] Lithium and its compounds are widely used in new energy, batteries, aerospace and other industries, and are known as the "energy element of the 21st century". As a country with lithium resources, my country's lithium resources are mainly found in lithium ore and brine, of which brine lithium resources account for more than 80%. The small reserves of lithium ore, low grade and high energy consumption of lithium extraction from ore are not conducive to green development. Salt lake brine has rich lithium resources, so lithium extraction from salt lakes has become the main development trend of lithium resource utilization in my country.
[0003] my country's salt lake brine lithium resources are characterized by low grade and high magnesium-lithium ratio, making lithium extraction difficult, which limits the development and utilization of salt lake lithium resources. At present, the methods for extracting lithium from salt lake brines mainly include calcination, solvent extraction, precipitation, membrane separation, adsorption, etc. Among them, the adsorption method has the advantages of high selectivity, low pollution, and high recovery rate, and has obvious advantages in extracting lithium from low-lithium-grade brine.
[0004] The core of lithium extraction by adsorption is to prepare lithium adsorbents with high selectivity, large adsorption capacity and good cycle stability. At present, the adsorbents used for lithium extraction from brine mainly include ion sieve oxides and aluminum salt lithium adsorbents. Among them, ion sieve oxides include manganese ion sieves and titanium ion sieves. However, manganese ion sieves have a high dissolution loss problem, and the application of titanium ion sieves is limited by their high cost. Aluminum salt lithium adsorbents have simple synthesis conditions, Li + It has the advantages of high selectivity, elution with water, and no pollution. Therefore, aluminum salt lithium adsorbent has become the only industrially applied lithium extraction adsorbent.
[0005] Patent publication number CN108993376A discloses a method for preparing an aluminum salt lithium adsorbent, which comprises mixing an aluminum salt and a lithium salt and dissolving them in deionized water, ultrasonically mixing them thoroughly, then dropping the mixed solution into an alkaline solution, or dropping the alkaline solution into a mixed solution, or dropping the mixed solution and the alkaline solution into a reactor in parallel, controlling pH aging, hydrothermal reaction, filtering and washing, vacuum drying, washing and drying with water to obtain an aluminum salt lithium adsorbent. However, the aluminum salt lithium adsorbent synthesized by this method has an Al(OH)3 impurity peak in the XRD analysis after elution, indicating that the adsorbent has structural collapse due to excessive elution, which affects the subsequent lithium extraction performance.
[0006] Publication 1 (Industrial & Engineering Chemistry Research, 2020, 59 (30): 13539-13548.) and Publication 2 (Journal of colloid and interface science, 2020, 572: 107-113.) both reported that under high liquid-to-solid ratio or high temperature elution conditions, the aluminum salt lithium adsorbent collapsed when over-eluted, the adsorbent was deactivated, and the adsorption capacity decreased. This shows that if the elution intensity is not enough, the Li + There are fewer active sites and a smaller adsorption capacity; however, if the elution intensity is too high, the aluminum salt lithium adsorbent structure will collapse and become inactive, and the adsorption capacity will decrease, seriously affecting its lithium extraction performance. Therefore, the elution problem of aluminum salt lithium adsorbent greatly limits its industrial application value.
[0007] In addition, compared with manganese and titanium ion sieves, the adsorption capacity of aluminum salt lithium adsorbent is generally low. From the molecular formula of aluminum salt lithium adsorbent LiCl·2Al(OH)3·XH2O, it can be seen that its theoretical maximum adsorption capacity is only 30mg / g. In actual application, the actual adsorption capacity of aluminum salt lithium adsorbent can only reach 25-50% of this value. On the one hand, in order to ensure the structural stability of aluminum salt lithium adsorbent, it is impossible to elute and release too much Li + active sites, on the other hand, the released effective Li + The low utilization rate of active sites leads to low actual adsorption capacity of aluminum salt lithium adsorbent, which greatly limits its further industrial application. Summary of the invention
[0008] One of the purposes of the present application is to provide a compound having the advantages of strong resistance to elution inactivation, fast adsorption rate, large adsorption capacity and high selectivity.
[0009] Another object of the present application is to provide a method for preparing the above-mentioned compound, which has the advantages of simple synthesis conditions, no need for high temperature and high pressure, low energy consumption, no need to add organic solvents, non-toxic and pollution-free, and green and environmentally friendly.
[0010] Another object of the present application is to provide the use of the above-mentioned compound in lithium extraction from salt lakes.
[0011] This application is implemented as follows:
[0012] The present application provides a compound, whose molecular formula is LiCl m X n- (1-m) / n ·aAl(OH)3·xH2O; where X is a radius greater than Cl -At least one of the anions having a radius of -5 to -1 and a valence of -5 to -1, a is 2 to 8, and x is 0.2 to 12.
[0013] In some optional embodiments, X is CO3 2- 、SO4 2- 、SO3 2- PO4 3- PO3 3- , BO4 3- 、DBS - DS - At least one of .
[0014] The present application also provides a method for preparing the above compound, which comprises the following steps:
[0015] Adding aluminum chloride and lithium chloride into deionized water and mixing evenly to obtain a first mixed solution;
[0016] Adding alkali and at least one anion salt into deionized water and mixing evenly to obtain a second mixed solution; the radius of the anion is larger than Cl - radius and valence is -5 to -1;
[0017] The first mixed solution is added dropwise to the second mixed solution and stirred for reaction, aged, filtered, dried once, washed with water to remove LiCl, and dried twice.
[0018] In some optional embodiments, the molar ratio of Li to Al in the first mixed solution is 0.2-5:2, and the concentrations of lithium chloride and aluminum chloride in the first mixed solution are 0.05-12.5 mol / L and 0.5-5 mol / L, respectively.
[0019] In some optional embodiments, the anion salt is selected from at least one of sodium carbonate, potassium carbonate, ammonium carbonate, sodium sulfate, potassium sulfate, ammonium sulfate, sodium sulfite, potassium sulfite, ammonium sulfite, sodium phosphate, potassium phosphate, ammonium phosphate, sodium phosphite, potassium phosphite, ammonium phosphite, sodium borate, potassium borate, ammonium borate, sodium acetate, potassium acetate, ammonium acetate, sodium dodecylbenzene sulfonate, potassium dodecylbenzene sulfonate, ammonium dodecylbenzene sulfonate, sodium dodecyl sulfate, potassium dodecyl sulfate, and ammonium dodecyl sulfate; the concentration of the anion salt in the second mixed solution is 0.01-10 mol / L; the alkali is selected from at least one of sodium hydroxide, potassium hydroxide, and ammonia water; the concentration of the alkali in the second mixed solution is 1-15 mol / L; and the pH of the second mixed solution is 9-14.
[0020] In some optional embodiments, the molar ratio of the anion salt to lithium chloride is 0.1-5:1.
[0021] In some optional embodiments, the volume ratio of the first mixed solution to the second mixed solution is 0.5-10:1.
[0022] In some optional embodiments, the stirring reaction temperature is 20-90° C., and the pH at the end point of the stirring reaction is 3-9; the aging temperature is 0-90° C., and the aging time is 0.1-24 h.
[0023] In some optional embodiments, the liquid-to-solid ratio of water washing is 10-1000 mL:1 g, the water washing temperature is 0-80° C., and the water washing time is 0.1-24 h.
[0024] The present application also provides the use of the above-mentioned compound as an adsorbent for lithium extraction that is resistant to elution and deactivation.
[0025] The beneficial effects of the present application are as follows: the present application provides a compound, a preparation method thereof and its application as an adsorbent for lithium extraction that resists elution inactivation, the compound has the advantages of strong anti-elution inactivation ability, fast adsorption rate, large adsorption capacity and high selectivity, and can be used as an adsorbent in lithium extraction from salt lakes. The preparation method of the compound has the advantages of simple synthesis conditions, no need for high temperature and high pressure, low energy consumption and no need to add organic solvents, non-toxic and pollution-free, and green and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0027] Figure 1 XRD patterns of the adsorbent prepared in Example 1 of the present application and the adsorbent prepared in the control group and eluted at a liquid-to-solid ratio of 100 mL / g and 500 mL / g;
[0028] Figure 2 The adsorbent prepared in Example 1 of the present application and the adsorbent prepared in the control group were added to the brine of Lop Nur Salt Lake for adsorption and then the Li in the brine at different reaction times was measured using an atomic absorption spectrometer. + The residual concentration was calculated and the adsorption capacity of the adsorbent was obtained.
[0029] Figure 3 XRD patterns of the adsorbents prepared in Example 2, Example 3 and the control group of the present application after elution at different liquid-to-solid ratios; DETAILED DESCRIPTION
[0030] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Therefore, the following detailed description of the embodiments of the present application provided in the drawings is not intended to limit the scope of the application claimed for protection, but merely represents the selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0031] The following is a further detailed description of the characteristics and performance of the compound of the present application, its preparation method and its application as an elution-resistant and inactivated lithium-extraction adsorbent in conjunction with the examples.
[0032] The present invention provides a compound having a molecular formula of LiCl m X n- (1-m) / n ·aAl(OH)3·xH2O; where X is a radius greater than Cl - At least one of the anions with a radius and a valence of -5 to -1, a is 2 to 8, and x is 0.2 to 12. Optionally, X is CO3 2- 、SO4 2- 、SO3 2- PO4 3- PO3 3- , BO4 3- , DBS-, DS-.
[0033] The present invention also provides a method for preparing the above compound, which comprises the following steps:
[0034] Aluminum chloride and lithium chloride are added to deionized water and mixed evenly to obtain a first mixed solution; optionally, the molar ratio of Li to Al in the first mixed solution is 0.2-5:2; optionally, the concentrations of lithium chloride and aluminum chloride in the first mixed solution are 0.05-12.5 mol / L and 0.5-5 mol / L, respectively.
[0035] Adding alkali and at least one anion salt into deionized water and mixing evenly to obtain a second mixed solution; the radius of the anion is larger than Cl -radius and a valence of -5 to -1; optionally, the anion salt is selected from at least one of sodium carbonate, potassium carbonate, ammonium carbonate, sodium sulfate, potassium sulfate, ammonium sulfate, sodium sulfite, potassium sulfite, ammonium sulfite, sodium phosphate, potassium phosphate, ammonium phosphate, sodium phosphite, potassium phosphite, ammonium phosphite, sodium borate, potassium borate, ammonium borate, sodium acetate, potassium acetate, ammonium acetate, sodium dodecylbenzene sulfonate, potassium dodecylbenzene sulfonate, ammonium dodecylbenzene sulfonate, sodium dodecyl sulfate, potassium dodecyl sulfate, and ammonium dodecyl sulfate; optionally, the concentration of the anion salt in the second mixed solution is 0.01 to 10 mol / L; optionally, the alkali is selected from at least one of sodium hydroxide, potassium hydroxide, and ammonia water; optionally, the concentration of the alkali in the second mixed solution is 1 to 15 mol / L; optionally, the pH of the second mixed solution is 9 to 14.
[0036] The first mixed solution is added dropwise to the second mixed solution and stirred for reaction, aged, filtered, dried once, washed with water to remove LiCl, and dried twice. Optionally, the molar ratio of the anion salt to lithium chloride is 0.1 to 5:1; optionally, the volume ratio of the first mixed solution to the second mixed solution is 0.5 to 10:1; optionally, the temperature of the stirring reaction is 20 to 90°C; optionally, the pH at the end of the stirring reaction is 3 to 9; optionally, the aging temperature is 0 to 90°C; optionally, the aging time is 0.1 to 24h. Optionally, the liquid-to-solid ratio of the water washing is 10 to 1000mL: 1g; optionally, the water washing temperature is 0 to 80°C; optionally, the water washing time is 0.1 to 24h.
[0037] Among them, BO4 3- 、DBS - DS - They refer to borate anion, dodecylbenzenesulfonate anion, and dodecylsulfate anion respectively.
[0038] The embodiments of the present application also provide the use of the above compounds in extracting lithium from salt lakes.
[0039] The preparation method of the compound provided in the embodiment of the present application is to generate an aluminum salt lithium adsorbent by coprecipitation method, + The insertion reaction is coupled with the self-assembly process of the layered structure of the adsorbent, and one or more specific anions such as CO3 are directly introduced into the interlayer of the adsorbent in one step. 2- 、SO4 2- 、SO3 2- PO4 3- PO3 3- , BO4 3- 、DBS - DS - These interlayer anions have a stronger affinity for the aluminum salt lithium adsorbent layer, and can transfer the corresponding charge amount of Li+ Anchored in the vacancies of the adsorbent layer, thereby inhibiting the Li + At the same time, due to the large radius of the above-mentioned specific anions, an aluminum salt lithium adsorbent with a large interlayer spacing will be formed during the self-assembly process of the layered structure. The expansion of the interlayer spacing is conducive to accelerating the transmission rate of ions and exposing more Li + The active sites of the adsorbent are increased, thereby increasing the adsorption capacity and adsorption rate of the adsorbent. The preparation method of the adsorbent provided in the embodiment of the present application has the advantages of simple synthesis conditions, no need for high temperature and high pressure, low energy consumption, no need for the addition of organic solvents, non-toxic and pollution-free, and green and environmentally friendly.
[0040] The molecular formula prepared in this application is LiCl m X n- (1-m) / n The compound of ·aAl(OH)3·xH2O has the advantages of strong resistance to elution deactivation. Under high elution intensity, there will be no over-elution and structural collapse. There is no generation of gibbsite or bayerite (Al(OH)3). There is no need to worry about the collapse of the adsorbent structure caused by excessive water washing. It has the advantages of fast adsorption rate, large adsorption capacity and high selectivity. It can be used as a lithium extraction adsorbent resistant to elution deactivation and applied to lithium extraction from salt lake brine.
[0041] Embodiment 1:
[0042] This embodiment provides a compound, which is prepared by the following method:
[0043] 6.72 g of AlCl3·6H2O and 0.5899 g of LiCl were dissolved in 20 mL of deionized water and mixed evenly to obtain a first mixed solution, wherein the molar ratio of Li to Al was 1:2, and the concentrations of aluminum and lithium in the first mixed solution were 1.4 mol / L and 0.7 mol / L, respectively;
[0044] 2.129 g Na3PO4·12H2O and 2.24 g NaOH were mixed in 10 mL deionized water to obtain a second mixed solution, wherein the concentration of Na3PO4 in the second mixed solution was 0.56 mol / L, the concentration of NaOH was 5.6 mol / L, and the molar ratio of sodium phosphate to lithium chloride was 0.4:1;
[0045] The first mixed solution was added dropwise to the second mixed solution for reaction, the volume ratio of the first mixed solution to the second mixed solution was 2:1, the stirring speed was 300 rpm, the reaction temperature of the entire reaction system was 80°C, the pH at the reaction end point was controlled to be 6, and the reaction was aged at 80°C for 1h after the reaction was completed. After the aging was completed, a suction filter was used for solid-liquid separation, and the obtained solid product was dried at 80°C for 12h. The molecular formula of the obtained aluminum salt lithium adsorbent was detected to be LiCl 0.5 (PO4) 1 / 6 ·2Al(OH)3·2H2O.
[0046] Control group
[0047] The control group provided an adsorbent. Except that Na3PO4·12H2O was not added, the other experimental conditions were the same as those in Example 1. The molecular formula of the obtained aluminum salt lithium adsorbent was detected to be LiCl·2Al(OH)3·2H2O.
[0048] The aluminum salt lithium adsorbent prepared in Example 1 and the aluminum salt lithium adsorbent prepared in the control group were eluted at a liquid-to-solid ratio of 100 mL / g and 500 mL / g (respectively denoted as L / S=100 and L / S=500) and a temperature of 40°C, respectively, and solid-liquid separation was performed using a suction filter, and the obtained solid product was dried at 80°C for 12 h.
[0049] The XRD patterns of the samples prepared in Example 1 and the control group and the samples eluted under the conditions of liquid-to-solid ratio of 100 mL / g and 500 mL / g are shown in Figure 1 .Depend on Figure 1 It can be seen that the peaks of the adsorbents prepared in Example 1 and the control group are sharper and correspond to the peaks of the existing aluminum salt lithium adsorbents. The XRD spectra of the samples eluted in Example 1 and the control group at a liquid-solid ratio of 100mL / g are basically unchanged compared to before elution. However, when the liquid-solid ratio increases to 500mL / g, a miscellaneous peak attributable to Al(OH)3 appears in the XRD spectrum of the control group sample, indicating that conventional aluminum salt lithium adsorbents are prone to excessive elution, causing their structure to collapse; however, the samples prepared in Example 1 have no other miscellaneous peaks in the aluminum salt lithium adsorbents eluted at liquid-solid ratios of 10mL / g and 500mL / g, indicating that the aluminum salt lithium adsorbent prepared in Example 1 of the present application has good resistance to excessive elution inactivation.
[0050] To further prove that the aluminum salt lithium adsorbent prepared in this application has good resistance to excessive elution inactivation, 1g of the aluminum salt lithium adsorbent obtained after activation under different elution conditions in Example 1 and the control group was added to 50mL of Lop Nur Salt Lake brine (the brine ion composition is shown in Table 1), placed in a constant temperature water bath oscillator at a frequency of 150rpm for reaction, and the Li in the brine at different reaction times was measured by atomic absorption spectrometer. + The residual concentration of the adsorbent is calculated as Figure 2 shown.
[0051] Depend on Figure 2 It can be seen that the adsorption capacity of the control group (L / S = 500) is significantly smaller than that of the control group (L / S = 100), indicating that the conventional aluminum salt lithium adsorbent is over-eluted and the structure collapses, resulting in a decrease in adsorption capacity, and Figure 1 The results of XRD are consistent; however, the adsorption capacity of Example 1 (L / S=500) is significantly greater than that of Example 1 (L / S=100). Combined with the XRD results, it is shown that the aluminum salt lithium adsorbent prepared in Example 1 of the present application has good resistance to elution deactivation, and the adsorption capacity and adsorption rate of the adsorbent are improved, with a maximum adsorption capacity of 9.35 mg / g at 180 min.
[0052] Table 1 Composition of brine in Lop Nur Salt Lake
[0053]
[0054] Embodiment 2:
[0055] This embodiment provides a compound, which is prepared by the following method:
[0056] 6.72 g of AlCl3·6H2O and 0.8849 g of LiCl were dissolved in 20 mL of deionized water and mixed evenly to obtain a first mixed solution, wherein the molar ratio of Li to Al was 1.5:2, and the concentrations of aluminum and lithium in the first mixed solution were 1.4 mol / L and 1.05 mol / L, respectively;
[0057] 2.84 g Na2SO4 and 6.4 g NaOH were mixed in 20 mL deionized water to obtain a second mixed solution, wherein the concentration of Na2SO4 in the second mixed solution was 1 mol / L, the concentration of NaOH was 8 mol / L, and the molar ratio of sodium sulfate in the second mixed solution to lithium chloride in the first mixed solution was 1:1.05;
[0058] The first mixed solution was added dropwise to the second mixed solution for reaction, the volume ratio of the first mixed solution to the second mixed solution was 1:1, the stirring speed was 300 rpm, the temperature of the entire reaction system was 70°C, the pH at the end point of the addition was controlled to be 6, and the reaction was aged at 80°C for 2h after the reaction was completed. After the aging was completed, the solution was filtered and dried at 80°C for 12h. The molecular formula of the obtained aluminum salt lithium adsorbent was detected to be LiCl 0.2 (SO4) 0.4 ·2Al(OH)3·2H2O.
[0059] The aluminum salt lithium adsorbent prepared in Example 2 and the aluminum salt lithium adsorbent prepared in the control group were eluted at a liquid-to-solid ratio of 400 mL / g (denoted as L / S=400) and a temperature of 30°C, and solid-liquid separation was performed using a suction filter, and the obtained solid product was dried at 80°C for 12 h.
[0060] The XRD patterns of the samples prepared in Example 2 and the control group after elution at a liquid-to-solid ratio of 400 mL / g are shown in Figure 3 When the eluent-solid ratio is 400 mL / g, a peak belonging to Al(OH)3 appears in the XRD spectrum of the control group sample, indicating that the conventional aluminum salt lithium adsorbent has the problem of excessive elution, resulting in its structural collapse; but the XRD spectrum of Example 2 has no other peaks, indicating that the aluminum salt lithium adsorbent prepared in Example 2 of the present application has good resistance to excessive elution deactivation. And in the sample of Example 2, d (003) The peak shifts to a smaller angle and the interlayer spacing increases. This is due to the larger radius of SO4 2- The interlayer spacing of the adsorbent is enlarged, which is beneficial to accelerate the ion transfer rate and expose more Li + Active sites increase the adsorption capacity and adsorption rate of the adsorbent.
[0061] To further prove that the aluminum salt lithium adsorbent prepared in this application has good resistance to excessive elution inactivation, 1g of the aluminum salt lithium adsorbent obtained after activation at an eluent-solid ratio of 400mL / g in Example 2 and the control group was added to 50mL of Lop Nur Salt Lake brine (the brine ion composition is shown in Table 1), and placed in a constant temperature water bath oscillator at a frequency of 150rpm for reaction. After adsorption equilibrium, the Li + The concentration of the adsorbent is calculated to obtain the equilibrium adsorption capacity Q e As shown in Table 2.
[0062] Embodiment 3:
[0063] This embodiment provides a compound, which is prepared by the following method:
[0064] 6.72 g of AlCl3·6H2O and 0.7374 g of LiCl were dissolved in 20 mL of deionized water and mixed evenly to obtain a first mixed solution, wherein the molar ratio of Li to Al was 1.25:2, and the concentrations of aluminum and lithium in the first mixed solution were 1.4 mol / L and 0.875 mol / L, respectively;
[0065] 3.485 g of sodium dodecylbenzene sulfonate (SDBS) and 3.2 g of NaOH were mixed in 10 mL of deionized water to obtain a second mixed solution, wherein the concentration of sodium dodecylbenzene sulfonate in the second mixed solution was 1 mol / L, the concentration of NaOH was 8 mol / L, and the molar ratio of sodium dodecylbenzene sulfonate to lithium chloride was 1:1.75;
[0066] The first mixed solution was added dropwise to the second mixed solution for reaction, the volume ratio of the first mixed solution to the second mixed solution was 2:1, the stirring speed was 300 rpm, the reaction temperature of the entire reaction system was 80°C, the pH at the reaction end point was controlled to be 6.5, and the reaction was aged at 80°C for 4h after the reaction was completed. After the aging was completed, a suction filter was used for solid-liquid separation, and the obtained solid product was dried at 80°C for 12h. The molecular formula of the obtained aluminum salt lithium adsorbent was detected to be LiCl 0.5 (DBS) 0.5 ·2Al(OH)3·2H2O.
[0067] The aluminum salt lithium adsorbent prepared in Example 3 and the aluminum salt lithium adsorbent prepared in the control group were eluted at a liquid-to-solid ratio of 800 mL / g (denoted as L / S=800) and a temperature of 60°C, and a vacuum filter was used for solid-liquid separation, and the obtained solid product was dried at 80°C for 12 h.
[0068] The XRD patterns of the samples prepared in Example 3 and the control group after elution at a liquid-to-solid ratio of 800 mL / g are shown in Figure 3 When the eluent-to-solid ratio is 800 mL / g, the XRD spectrum of the control group sample shows obvious and large amounts of impurity peaks attributable to Al(OH)3, indicating that the aluminum salt lithium adsorbent with a higher content has transformed into Al(OH)3 and its structure has collapsed; however, the XRD spectrum of Example 3 does not have other impurity peaks, indicating that the aluminum salt lithium adsorbent prepared in Example 3 of the present application has good resistance to excessive elution deactivation. And in the sample of Example 3, d (003) The peak of the sample in Example 2 shifts to a smaller angle and the interlayer spacing increases further. This is because the DBS with a larger radius - The interlayer spacing of the adsorbent is enlarged, which is beneficial to accelerate the ion transfer rate and expose more Li + Active sites increase the adsorption capacity and adsorption rate of the adsorbent.
[0069] To further prove that the aluminum salt lithium adsorbent prepared in this application has good resistance to excessive elution inactivation, 1g of the aluminum salt lithium adsorbent obtained after activation at an eluent-solid ratio of 400mL / g in Example 3 and the control group was added to 50mL of Lop Nur Salt Lake brine (the brine ion composition is shown in Table 1), and placed in a constant temperature water bath oscillator at a frequency of 150rpm for reaction. After adsorption equilibrium, the Li in the brine before and after adsorption was measured by atomic absorption spectrometer. + The concentration of the adsorbent is calculated to obtain the equilibrium adsorption capacity Q e As shown in Table 2.
[0070] Table 2 Equilibrium adsorption capacity of the compounds prepared in the examples and control groups for salt lake brine
[0071]
[0072] Embodiment 4:
[0073] This embodiment provides a compound, which is prepared by the following method:
[0074] 6.72 g of AlCl3·6H2O and 0.7374 g of LiCl were dissolved in 20 mL of deionized water and mixed evenly to obtain a first mixed solution, wherein the molar ratio of Li to Al was 1.25:2, and the concentrations of aluminum and lithium in the first mixed solution were 1.4 mol / L and 0.875 mol / L, respectively;
[0075] 1.442 g sodium dodecyl sulfate (SDS), 0.8712 g K2SO4 and 3.2 g NaOH were mixed in 10 mL deionized water to obtain a second mixed solution, wherein the concentration of SDS in the second mixed solution was 0.5 mol / L, the concentration of K2SO4 was 0.5 mol / L, the concentration of NaOH was 8 mol / L, and the molar ratio of sodium dodecyl sulfate and potassium sulfate in the second mixed solution to lithium chloride in the first mixed solution was 0.5:0.5:1.75;
[0076] The first mixed solution was added dropwise to the second mixed solution for reaction, the volume ratio of the first mixed solution to the second mixed solution was 2:1, the stirring speed was 300 rpm, the temperature of the entire reaction system was 60°C, the pH at the end point of the addition was controlled to be 7, and the reaction was aged at 60°C for 4h after the reaction was completed. After the aging was completed, the mixture was filtered and dried at 80°C for 12h. The molecular formula of the obtained aluminum salt lithium adsorbent was detected to be LiCl 0.4 (SO4) 0.2 (DS) 0.2 ·2Al(OH)3·2H2O.
[0077] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents the selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
Claims
1. A compound, characterized in that The molecular formula is LiCl m X n- (1-m) / n ·aAl(OH)3· x H2O; where X is a radius greater than Cl - At least one of the anions with a radius and a valence of -5 to -1, a is 2 to 8, x is 0.2~12; X is CO3 2- 、SO4 2- 、SO3 2- PO4 3- PO3 3- , BO4 3- 、DBS - DS - At least one of; m is 0.2~0.5; BO4 3- 、DBS - DS - They refer to borate anion, dodecylbenzenesulfonic acid anion, and dodecylsulfuric acid anion, respectively.
2. The compound according to claim 1, characterized in that The anion salt of X is selected from at least one of sodium carbonate, potassium carbonate, ammonium carbonate, sodium sulfate, potassium sulfate, ammonium sulfate, sodium sulfite, potassium sulfite, ammonium sulfite, sodium phosphate, potassium phosphate, ammonium phosphate, sodium phosphite, potassium phosphite, ammonium phosphite, sodium borate, potassium borate, ammonium borate, sodium dodecylbenzene sulfonate, potassium dodecylbenzene sulfonate, ammonium dodecylbenzene sulfonate, sodium dodecyl sulfate, potassium dodecyl sulfate, and ammonium dodecyl sulfate.
3. Use of the compound according to claim 1 or 2 as an adsorbent for lithium extraction that is resistant to elution and inactivation.
Citation Information
Patent Citations
Aluminum salt lithium adsorbent, and preparation method and application thereof
CN108993376A
Process method for extracting Mg and Li from bittern and simultaneously producing hydrotalcite
CN105152193A
Recycling method for mother liquor of salt lake brine lithium extraction
CN110078102A